Apple Inc. / Nur A’fyfah Zaimy - Zaimy, Nur A’fyfah (2022)
This is an attempt to know the theories can be applied to practical situations. As a student in UiTM Arau, Perlis, it is a part of the study for everyone to undergo a case study project. For this purpose, I got an opportunity to found a company which is Apple Inc, a big technology company that is currently based in Cupertino, California, United States. In the first part of this case study, all the general information of the company has been collected. Information is gathered through the Google search engine at Apple website and other related articles. Meanwhile, the second part of this case study contains the specialized subject study. The objective of the case study is to work on the company background, organizational structure, products and services that Apple Inc. provides. Next, I study about the technology of the Apple watch and the finding of the product. The major problem faced by the product is the lack of IoT sensors in the Apple watch to detect the presence of migraines. Finally, I also study the strategy used by the company to promote their highly fascinating products. Goals indicate what a business unit wants to achieve. Strategy is an action plan to get the goal to accomplish. Every entrepreneur must design a strategy to achieve the goal that consists of marketing strategy and effective management. I also analyzed the strength, weaknesses, opportunities and threats of the product by using SWOT analysis.